Post-transcriptional Regulation of Colorectal Cancer: A Focus on RNA-Binding Proteins - García-Cárdenas, Jennyfer M.; Guerrero, Santiago; López-Cortés, Andrés; Armendáriz-Castillo, Isaac; Guevara-Ramírez, Patricia; Pérez-Villa, Andy; Yumiceba, Verónica; Zambrano, Ana Karina; Leone, Paola E.; Paz-y-Miño, César (Frontiers in Molecular Biosciences, 2019)
Colorectal cancer (CRC) is a major health problem with an estimated 1. 8 million new cases worldwide. To date, most CRC studies have focused on DNA-related aberrations, leaving post-transcriptional processes under-studied. However, post-transcriptional alterations have been shown to play a significant part in the maintenance of cancer features. RNA binding proteins (RBPs) are uprising as critical regulators of every cancer hallmark, yet little is known regarding the underlying mechanisms and key downstream oncogenic targets. Currently, more than a thousand RBPs have been discovered in humans and only a few have been implicated in the carcinogenic process and even much less in CRC. Identification of cancer-related RBPs is of great interest to better understand CRC biology and potentially unveil new targets for cancer therapy and prognostic biomarkers. In this work, we reviewed all RBPs which have a role in CRC, including their control by microRNAs, xenograft studies and their clinical implications.